2021
DOI: 10.1038/s41443-021-00422-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial care and support in the field of intersex/diverse sex development (dsd): counselling experiences, localisation and needed improvements

Abstract: From different sides, there is a call for better psychosocial care and counselling in the field of diverse sex development (dsd). However, studies on the specific demands, deficits and needed improvements regarding those services are rare. This exploratory online study aimed at investigating counselling experiences and the ideas that different groups of participants have concerning the localisation of counselling structures and improving care. Quantitative and qualitative data (N = 630) were analysed within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
4
11
0
Order By: Relevance
“…The wish to hold a position of medical control was also reflected in the sceptical attitude of most participants with regard to the function of support and advocacy groups in the care of intersex persons. Although it would be highly beneficial for intersex youth if non-medical perspectives would be taken into account, at present non-medical partners are hardly included in the MDT [20,21]. Likewise, in line with other studies [18] our results suggest that the representation within the MDT of different types of care professionals (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The wish to hold a position of medical control was also reflected in the sceptical attitude of most participants with regard to the function of support and advocacy groups in the care of intersex persons. Although it would be highly beneficial for intersex youth if non-medical perspectives would be taken into account, at present non-medical partners are hardly included in the MDT [20,21]. Likewise, in line with other studies [18] our results suggest that the representation within the MDT of different types of care professionals (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…The Consensus Statement and its update [1,11]havecalledfortheintegration of psycho-social support in the care of intersex persons. Research, however, has revealed an important gap between these intentions and available mental health services for children and adults with VSC and their families [19,20]. The present study offers an important contribution to the existing literature on support services by examining the perspective of HCPs who care for intersex youth in Switzerland.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As intersex conditions are rare, parents of such children and later the individuals themselves may experience their situation as unique and very difficult for others to understand. Thus, based on clinical experience, there is a consensus among HCPs who are experienced in intersex care, that social support is a crucial component of intersex care, not only through professional support by MHPs (Pasterski et al., 2010 ), but also, importantly, through support groups of individuals with intersex conditions (Baratz et al., 2014 ; Cull & Simmonds, 2010 ; Hughes et al., 2006; Lampalzer et al., 2021 ). A detailed international listing of DSD and intersex peer support and advocacy groups with their websites has been provided by Lee, Nordenström et al.…”
Section: Chapter 10 Intersexmentioning
confidence: 99%
“…It should be clear, frank and honest. (51)(52)(53)(54) The need for encounter and exchange ideas with other parents with similar experience with DSD are found to be helpful. Furthermore, there is a need for a continuous physiological support and counseling.…”
Section: Discussion On Issues Related To Ambiguity Of Genitaliamentioning
confidence: 99%